2020
DOI: 10.1007/s40519-020-01051-x
|View full text |Cite
|
Sign up to set email alerts
|

Drunkorexia: is it really “just” a university lifestyle choice?

Abstract: Purpose The current study investigated the prevalence of compensatory behaviours (caloric restriction, increased exercise and bulimic tendencies) in response to alcohol consumption (also known as Drunkorexia) in students, non-students and previous students, as well as beginning to understand the presence of possible predictors of these behaviours (body esteem, sensation seeking). Methods A volunteer sample of students, non-students and previous students (n = 95) completed the Compensatory Eating and Behaviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 42 publications
5
20
0
Order By: Relevance
“…Those stated that sensation seeking has either no association with later bulimic symptoms [13] or that it is a weakly protective factor [12]. However, our findings are supported by cross-sectional meta-analyses based on clinical samples [1,15] and other studies with limited populations, such as university students [2,[16][17][18], which all show that sensation seeking is positively correlated with bulimic symptoms. Previous studies have not considered the possible gender differences.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Those stated that sensation seeking has either no association with later bulimic symptoms [13] or that it is a weakly protective factor [12]. However, our findings are supported by cross-sectional meta-analyses based on clinical samples [1,15] and other studies with limited populations, such as university students [2,[16][17][18], which all show that sensation seeking is positively correlated with bulimic symptoms. Previous studies have not considered the possible gender differences.…”
Section: Discussionsupporting
confidence: 62%
“…Most of the existing community studies have shown either no association between sensation seeking and bulimic symptoms [10,11,13] or a mild negative correlation [12], and only one with a cross-sectional setting a positive correlation even after controlling for other psychiatric comorbidities such as victimization experiences and post-traumatic stress disorder (PTSD) [14]. These findings differ from some studies based on clinical samples [1,15] or other limited populations, such as university students [2,[16][17][18], which indicate that sensation seeking is positively correlated with bulimic symptoms. However, when comparing these results to the present study, it is notable that only one of the previous studies used the eating disorder inventory-2 (EDI-2) Bulimia subscale to measure bulimic symptoms [16].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Indeed, FAD is typical of individuals who choose to engage in diet-related behaviors before or after drinking large amounts of alcohol, to compensate for calories consumed through alcoholic beverages for the fear of gaining weight, or to enhance the intoxicating effects of alcohol [ 18 , 21 , 22 ]. Recently, researchers have proven that FAD is predicted by poor body esteem, high sensation seeking [ 23 , 24 ], and drive for thinness [ 25 ], thus suggesting that people may use this at-risk behavior to pursue an idealized body image. Moreover, in recent studies [ 26 ], FAD appeared to be driven by motivations analogous to eating and substance use disorders: applying the Cooper’s alcohol motivation model, researchers found that enhancement and conformity motives were both related with compensatory behaviors, suggesting that young adults may limit their caloric intake on drinking days to comply with social expectations and to be accepted by others [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Individuals who engage in this unhealthy pattern of behaviors may be also motivated to increase the effects of intoxication through the engagement in disordered eating [2]. Disordered eating (e.g., skipping meals, caloric restriction) prior to consumption of alcohol can increase the effects of intoxication [7]. Prior literature examing FAD behaviors has shown that some individuals have engaged in disordered eating patterns prior to consuming alcohol to increase the effects of alcohol [1,2,[4][5][6].…”
Section: Introductionmentioning
confidence: 99%